The effects of exercise interventions on depressive symptoms in stroke patients: a systematic review and meta-analysis - Wang, Zhi-Yuan; Deng, Ya-Lu; Zhou, Ting-Yuan; Jiang, Zi-Yang; Liu, Yi; Liu, Bo-Fu; Cao, Yu (Frontiers in Physiology, 2025)
PurposeThis systematic review and meta-analysis aimed to evaluate the effects of exercise interventions on depressive symptoms in stroke patients.MethodsFollowing PRISMA guidelines, We conducted searches in PubMed, Embase, CENTRAL, and Web of Science. The topic was the effect of exercise on depression levels in stroke patients. Patient’s performance on depression scales after exercise was assessed using standardized mean difference (SMD) and 95% confidence intervals (95% CI). A random effects model (RE) was used to conduct a meta-analysis and compare the results between subgroups conducted based on adherence to ACSM guidelines and the length of exercise interventions.ResultsThe analysis included 24 randomized controlled trials (RCTs) involving 1,757 participants. The meta-analysis revealed that exercise interventions had a significant positive effect on reducing depressive symptoms in stroke patients, with a standardized mean difference (SMD) of −0.43 (95% CI: 0.65, −0.21). Subgroup analysis indicated that high compliance with ACSM guidelines resulted in a more substantial reduction in depressive symptoms (SMD = −0.79, 95% CI: 1.10, −0.49), compared with low or uncertain compliance (SMD = −0.03, 95% CI: 0.16, 0.10). Longer exercise intervention was associated with greater mitigation of depressive symptoms. The differences between intervention groups of different lengths were statistically significant (p < 0.05).ConclusionThese findings support the integration of tailored exercise programs into post-stroke care to optimize mental health outcomes. Compliance to ACSM-recommended exercise dosages significantly ameliorate depression levels in stroke patients. Further research is warranted to explore standardized exercise regimens in larger, multicenter trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, identifier PROSPERO(CRD42024579095).